2013
DOI: 10.1017/s0033822200058197
|View full text |Cite
|
Sign up to set email alerts
|

Origin of Subsoil Carbon in a Chinese Paddy Soil Chronosequence

Abstract: Rice paddies are highly important agricultural soils in view of their relevance as major staple food provider in the world and their key role in the global carbon cycle, caused by special management practices. A soil chronosequence, consisting of paddy and upland soils, developed on reclaimed estuarine sediments in the Province of Zhejiang, China, was sampled to investigate the influence of duration of agricultural use (50 to 2000 yr) on soil composition. The uniform composition of the parent material provides… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 55 publications
0
10
0
Order By: Relevance
“…It is estimated that a 40% increase in rice production is needed to meet the surging demand from the rapidly increasing population by the end of 2030 [7,8]. China is the world's largest rice producer, accounting for 30% of total world production, with 29, 850 ha [9], followed by India (22%), Indonesia (9%), and Bangladesh (7%) [3,10]. On the other hand, paddy field, as constructed wetland ecosystems, plays an irreplaceable role in flood storage and detention, groundwater replenishment, environmental protection, and ecological balance maintenance [3].…”
Section: Introductionmentioning
confidence: 99%
“…It is estimated that a 40% increase in rice production is needed to meet the surging demand from the rapidly increasing population by the end of 2030 [7,8]. China is the world's largest rice producer, accounting for 30% of total world production, with 29, 850 ha [9], followed by India (22%), Indonesia (9%), and Bangladesh (7%) [3,10]. On the other hand, paddy field, as constructed wetland ecosystems, plays an irreplaceable role in flood storage and detention, groundwater replenishment, environmental protection, and ecological balance maintenance [3].…”
Section: Introductionmentioning
confidence: 99%
“…The lower δ 13 C of the WR5 and WR30 samples suggests that SOM derived from rice (and weeds) had become the major C pool in the silt/clay fraction several years after rice cultivation was started. Bräuer et al [] also reached a similar conclusion based on 14 C levels. The δ 13 C of silt/clay C in the soils with >1000 years of estimated period as a rice paddy was generally < −28‰ and lower than that in the soils with a shorter rice paddy history.…”
Section: Discussionmentioning
confidence: 99%
“…However, if the estimated MRT (<100 years under the field temperature conditions) were true, the 14 C concentration would have been higher due to the influence of atomic bomb experiments. Bräuer et al [] reported that the 14 C concentration of the humin fraction from the 1–19 cm depth layer of tidal flat sediments in the west zone of Hangzhou Bay was 55–57 pMC, although their fractionation method was more extensive than ours. If their average value (56 pMC) and the atmospheric 14 C concentration in 2008 (105 pMC) [ Levin et al , ] were applied to the sediment‐derived and rice‐ and weed‐derived C in the WR5 silt/clay‐humin, respectively, the proportion of C derived from sediment was estimated to be 58%, equivalent to 3.0 g C kg −1 soil.…”
Section: Discussionmentioning
confidence: 99%
“…The signal of bomb radiocarbon in the deep subsoil (Baisden and Parfitt 2007) may imply that deep carbon (C) is not completely passive. Young and fresh organic matter, introduced from the top through the direct input of fresh plant remains (Bräuer et al 2013a), stabilized-dissolved organic matter (Kalbitz et al 2005; Hanke et al 2014), and shoot roots and root exudates (Kuzyakov and Domanski 2000), may add fresh photosynthate to older subsoil organic matter and result in younger average 14 C concentrations. This supports other findings indicating that fresh organic C inputs tend to reactivate, microbially stable organic C in the deep soil layers (Fontaine et al 2004, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…As part of Research Unit 995, “Biogeochemistry of Paddy Soil Evolution,” we research paddy soils in both subtropical (phase 1) and tropical environments (phase 2). In phase 1, work on a soil chronosequence, derived from marine sediments in a subtropical area, demonstrated slower refreshment of old OC with fresh, plant-derived C in rice paddies than in non-paddies (“upland soils”), and a fast increase of OC in the top soil, already after 50 yr of cultivation (Bräuer et al 2013a). Now, in the second phase the studies focus on three different soil types in a tropical climate.…”
Section: Introductionmentioning
confidence: 99%